Forming and establishing the philosophical understanding of freedom in the history of European thought - Zoya Shwed (Cхід, 2013)
The article analyses the process of forming basic approaches to understanding "freedom". Established: The results of the philosophical analysis of this phenomenon can be accepted as a methodological principle for interpreting "ethno-religio-genesis" in Religiology (Knowledge of Religion).